Laissez-faire Technique in Periocular Reconstructive Surgery following Tumour Resection - Linntam, Delis; Klett, Artur (Klinische Monatsblätter für Augenheilkunde, 2022)
The laissez-faire technique, although not widely used by oculoplastic surgeons, is a valuable option in the reconstruction of periocular defects following tumour resection. In the authorsʼ experience, the most suitable location is the medial canthal area. Primary surgery is often simpler and better tolerated by the patient compared with alternative, more complex surgical procedures. The final functional and cosmetic outcome is highly dependent on patient selection and for an excellent result, certain modifications in surgical technique and additional manipulations in the early postoperative period must be considered. The technique is not usually the first choice, due to fear of a prolonged and complicated wound healing period. The unpredictability of the results may also be of concern to oculoplastic surgeons. This case series illustrates some modifications of surgery and postoperative care that can help optimise the outcome and reduce postoperative complications. As wound healing and scarring are influenced by contraction in the wound bed, tension guiding sutures are a valuable adjunct to laissez-faire techniques. They improve the predictability of the result after healing, and this is important primarily in reducing the risk of cicatricial ectropium, but also in the cosmetic result. Although there is a risk of infection with any open wound, in general, thorough patient education usually suffices to avoid postoperative complications. Appropriate wound care in the laissez-faire technique is fairly simple and easily achievable.
Keywords: laissez-faire; periocular tumor; reconstruction; secondary intention